The Impact of Soft-Skills Training for Entrepreneurs in Jamaica - Diego Ubfal; Irani Arraiz; Diether Beuermann; Michael Frese; Alessandro Maffioli; Daniel Verch (Institute of Labor Economics (IZA), 2019)
A randomized control trial with 945 entrepreneurs in Jamaica shows positive shortterm impacts of soft-skills training on business outcomes. The effects are concentrated among men, and disappear twelve months after the training. We argue that the main channel is increased adoption of recommended business practices, exclusively observed in the short run. We see persistent effects on an incentivized behavioral measure of perseverance after setbacks, a focus of this training. We compare a course focused only on soft-skills to one that combines soft-skills training with traditional business training. The effects of the combined training are never statistically significant.
Keywords: J24; L25; M13; O12; 330; business training; entrepreneurship; soft skills